Suppressive Effects of Cooling Compounds Icilin on Penicillin G-Induced Epileptiform Discharges in Anesthetized Rats - Moriyama, Hiroshi; Nomura, Sadahiro; Kida, Hiroyuki; Inoue, Takao; Imoto, Hirochika; Maruta, Yuichi; Fujiyama, Yuichi; Mitsushima, Dai; Suzuki, Michiyasu (Frontiers in Pharmacology, 2019)
More than 30% of patients with epilepsy are refractory and have inadequate seizure control. Focal cortical cooling (FCC) suppresses epileptiform discharges (EDs) in patients with refractory focal cortical epilepsy. However, little is known about the mechanism by which FCC inhibits seizures at 15°C, and FCC treatment is highly invasive. Therefore, new antiepileptic drugs are needed that produce the same effects as FCC but with different mechanisms of action. To address this need, we focused on transient receptor potential melastatin 8 (TRPM8), an ion channel that detects cold, which is activated at 15°C. We examined whether TRPM8 activation suppresses penicillin G (PG)-induced EDs in anesthetized rats. Icilin, a TRPM8 and TRPA1 agonist, was administered after PG injection, and a focal electrocorticogram (ECoG) and cortical temperature were recorded for 4 h. We measured spike amplitude, duration, firing rate, and power density in each band to evaluate the effects of icilin. PG-induced EDs and increased delta, theta, alpha, and beta power spectra were observed in the ECoG. Icilin suppressed EDs while maintaining cortical temperature. In particular, 3.0 mM icilin significantly suppressed PG-induced spike amplitude, duration, and firing rate, and improved the increased power density of each band in the EDs to the level of basal activity in the ECoG. These suppressive effects of 3.0-mM icilin on EDs were antagonized by administering N-(3-aminopropyl)-2-[(3-methylphenyl) methoxy]-N-(2-thienylmethyl)-benzamide hydrochloride (AMTB), a selective TRPM8 inhibitor. Our results suggest that TRPM8 activation in epileptic brain regions may be a new therapeutic approach for patients with epilepsy.